Capital Taxation and Imperfect Competition: ACE vs. CBIT - Kurt R. Brekke; Armando J. Garcia-Pires; Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies the market and welfare effects of two main tax reforms - the Corporate Business Income Tax (CBIT) and the Allowance for Corporate Equity tax (ACE). Using an imperfect-competition model for a small open economy, it is shown that the well-known neutrality property of ACE does not hold. Both corporate tax regimes distort market entry and equilibrium prices. A main result is that a small open economy should levy a positive source tax on capital in markets with free firm entry. Which tax system is better from a welfare point of view, depends on production technology, the competitive effects of ACE and CBIT, and whether entry is excessive or suboptimal at the given corporate tax rate. Imposing tax income neutrality yields a higher corporate tax rate with ACE, which increases the scope for CBIT to be welfare improving.
Keywords: D43; H25; 330; optimal corporate taxation; corporate tax reform; imperfect competition; ACE; CBIT